Integrating security into university operations: A case for TM forum’s open digital architecture in higher education - Regvart, Damir; Ogrizek, Ivana Biškupić; Kapulica, Ana (Edelweiss Applied Science and Technology, 2025)
Secure, scalable, and flexible digital ecosystems are becoming increasingly important as universities undergo a digital transition. The Open Digital Architecture (ODA) framework from the TM Forum provides a platform for modernizing digital services and telecommunications operations, with essential applications in higher education. This study investigates the effective use of ODA's cloud-native, modular, and interoperable components to improve security in university operations. This paper examines how ODA's security capabilities may address issues specific to higher education by connecting ODA components to essential university operations, including research data protection, student lifecycle management, and campus-wide applications.